First-line ribociclib plus letrozole in postmenopausal women with HR+ , HER2- advanced breast cancer: Tumor response and pain reduction in the phase 3 MONALEESA-2 trial - Janni, Wolfgang; Alba, Emilio; Bachelot, Thomas; Diab, Sami; Gil-Gil, Miguel; Beck, Thaddeus J; Ryvo, Larisa; Lopez, Rafael; Tsai, Michaela; Esteva, Francisco J; Auñón, Pilar Zamora; Kral, Zdenek; et al. (Breast cancer research and treatment, 2018)
PURPOSE: The phase 3 MONALEESA-2 study demonstrated that addition of ribociclib (RIB) to letrozole (LET) significantly improved progression-free survival (PFS) in patients (pts) with hormone receptor-positive (HR+), HER2-negative (HER2-) advanced breast cancer (ABC). Here, we evaluated duration of response (DoR), tumor shrinkage, PFS by treatment-free interval (TFI), and health-related quality of life (HRQoL). METHODS: Postmenopausal women (N = 668) with HR+ , HER2- ABC and no prior systemic therapy for ABC were randomized to RIB (600 mg/day; 3 weeks on/1 week off) plus LET (2.5 mg/day; continuous) or placebo (PBO) plus LET. Primary end point was PFS; HRQoL was the secondary end point; DoR was exploratory end point and PFS by TFI was post hoc analysis. RESULTS: Of 501 pts with measurable disease and confirmed complete or partial response, median DoR was 26.7 months (95% CI, 24.0-NR) in the RIB arm versus 18.6 months (95% CI, 14.8-23.1) in the PBO arm. At 8 weeks, more pts in the RIB arm (32%) versus the PBO arm (17%) experienced best percentage change ≥ 60%. The average pain reduction was greater in the RIB arm (26%) versus the PBO arm (15%). PFS benefit was seen with RIB vs PBO, irrespective of TFI. CONCLUSION: RIB plus LET versus PBO plus LET is associated with earlier and more durable tumor response, greater degree of tumor shrinkage and pain reduction, and PFS benefit irrespective of TFI. These data further support RIB plus LET as a first-line treatment option for postmenopausal women with HR+ , HER2- ABC.
Keywords: Neoplasm Staging; Receptors, Estrogen; dospělí; metastázy nádorů; Kaplan-Meier Estimate; nádory prsu; Female; Quality of Life; Adult; výsledek terapie; ženské pohlaví; Kaplanův-Meierův odhad; mladý dospělý; Aminopyridines; puriny; kvalita života; lidé; staging nádorů; Breast Neoplasms; Receptors, Progesterone; receptory progesteronu; receptory pro estrogeny; Aged, 80 and over; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Receptor, ErbB-2; Middle Aged; receptor erbB-2; nádorové biomarkery; Aged; Young Adult; Letrozole; Purines; Biomarkers, Tumor; lidé středního věku; senioři nad 80 let; senioři; Neoplasm Metastasis; letrozol; aminopyridiny; Humans